Longitudinal Changes in Diffusion Tensor Imaging Following Mild Traumatic Brain Injury and Correlation With Outcome - Yin, Bo; Li, Dan-Dong; Huang, Huan; Gu, Cheng-Hui; Bai, Guang-Hui; Hu, Liu-Xun; Zhuang, Jin-Fei; Zhang, Ming (Frontiers in Neural Circuits, 2019)
The chronic consequences of traumatic brain injury (TBI) may contribute to the increased risk for early cognitive decline and dementia, primarily due to the diffusion axonal injury. Previous studies in mild (mTBI) have been controversy in describing the white matter tracts integrity changes occurring at acute and sub-acute post-injury. In the prospective longitudinal study, we aim to investigate the longitudinal changes of white matter using diffusion tensor imaging (DTI) and their correlations with neuropsychological tests. Thirty-three patients with sub-acute mTBI, 31 matched healthy controls were studied with an extensive imaging and clinical battery. Neuroimaging was obtained within 7 days post-injury for acute scans and repeated at 1 month and 3 month post-injury. Using a region-of-interest-based approach, Tract-Based Spatial Statistics was used to conduct voxel-wise analysis on diffusion changes in mTBI and was compared to those of healthy matched controls, scanned during the same time period and rescanned with a similar interval as that of patients. We found decreased FA values in the left anterior limb of internal capsule (ALIC) and right inferior fronto-occipital fasciculus (IFOF) during the 7 days post-injury, which showed longitudinal evidence of recovery following one-month post-injury. Increased FA values in these two tracts at 1 month post-injury was positively associated with better performance on cognitive information processing speed at initial assessment. By contrast, there were also some tracts (right anterior corona radiata, forceps major and body of corpus callosum) exhibiting the continuing loss of integrity sustaining even beyond 3 months, which can predict the persisting post-concussion syndromes. Continuing loss of structural integrity in some tracts may contribute to the persistent post-concussion syndromes in mTBI patients, suggesting certain tracts providing an objective biomarker for tracking the pathological recovery process following mTBI.